1999
DOI: 10.1159/000030444
|View full text |Cite
|
Sign up to set email alerts
|

Penile Prosthesis Implantation and Couple’s Satisfaction

Abstract: Objective: Implant surgery is the most acceptable curative choice for patients with erectile dysfunction and their partners, since the results are excellent with regard to the couple’s pleasure and the materials used are extremely manageable Materials and Methods: We performed 46 prosthesis implantations in patients with erectile dysfunction: in 22 patients we implanted soft prostheses; in 20 malleable prostheses; in 1 a mono-component prosthesis, and in 3 patients a tri-component model. All patients and partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2001
2001
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 8 publications
2
21
0
1
Order By: Relevance
“…This may actually represent the patient's awareness of a lack of glanular engorgement, or a true decrease in girth and length [3]. Penile implants are placed in the corpora cavernosa displacing corporeal erectile tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may actually represent the patient's awareness of a lack of glanular engorgement, or a true decrease in girth and length [3]. Penile implants are placed in the corpora cavernosa displacing corporeal erectile tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Penile implants are placed in the corpora cavernosa displacing corporeal erectile tissue. The glans penis is not involved [3]. It is not unusual for patients who have penile implants to report some engorgement of the penile shaft and glans penis on sexual excitement but the glans penis does not get as firm as they desire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Thirdly, the satisfaction of prosthesis-assisted sexuality may be altered by psychological and relational factors. Several studies indicate that the least satisfaction was found in patients who are the most aware of the 'unnatural' aspect of the prosthesis (Montorsi et al, 2000;Porena et al, 1999). ln the same way, Collins and Kinder (1984) and Schover and Von Eschenbach (1985) argue that low satisfaction is characteristic of couples with important conflicts or with sexual desire troubles.…”
Section: Introductionmentioning
confidence: 99%